Impact of NFT technology on (fashion) B2C e-commerce brands - Lora, David; Ryška, Tomáš, 1976-; Yang, Hailey; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Non-Fungible-Tokens (NFTs) have gathered attention mainly due to becoming an asset class that has reached a trading volume of 23 billion USD in 2021, a 230x increase from a trading volume of 100 million USD in 2020. (The Block, 2021) The primary purpose of this thesis is to understand the implications this technology has for direct-to-consumer eCommerce businesses. The fundamental technology behind NFTs allows its user to prove ownership of a digital asset, and multiple applications of this technology are just being created. The process to achieve this objective will be, first, to review the available literature to assess the current state of the art of NFT technology and its current use cases in eCommerce. Second, to create a reference class of successful projects to understand the key drivers behind an effective implementation of this technology. And lastly, to perform qualitative research to understand the drivers for success from both the business and the consumer point of view.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses